THE IMPACT OF ENSO ON FARMERS HOUSEHOLD INCOME IN THE IMPENSO AREA OF CENTRAL SULAWESI PROVINCE - Arifuddin Lamusa; Hadayani Hadayani; Abdul Syakur; Ramal Yusuf (Universitas Tadulako, 2019)
The research objective was to identify the impact of enso towards households’ farmer income in impenso region. Data were collected from 250 farmer households which were randomly selected in ten villages at six subdistricts of Donggala Regency. All the farmers were interviewed with an aid of questionnaire. Data collected were tabulated and analysed using a multiple regresion model. Dummy variable was applied to identify the impact of enso towards households’ farmer income. The analysis showed that R2 was 60.9% with an F-value of 139, indicating that there was the impact of enso on households' farmer income. The households’ farmer income in the year without enso was shown to be higher than that in the year with enso.